PENINGKATAN HASIL BELAJAR KPK DAN FPB MELALUI PENDEKATAN KOOPERATIF MODEL JIGSAW DI V SD - Pasinggi, Yonathan Saba' (Universitas Negeri Makassar, 2015)
This study aims to determine whether the application of the model jigsaw cooperative approach can improve student learning outcomes of the KPK and FPB in class IV SDN Pasrepare City . This type of research is a classroom action research . Data was analyzed by descriptive qualitative . The results showed an increase seen from the results of the evaluation in mind that the average value obtained by students in the first cycle has not reached mastery . In the second cycle of evaluation results is known that the average value obtained was significantly increased but not yet complete . The third cycle of evaluation results is known that the average value obtained by students has exceeded the value of completeness .